Analysis of User Satisfaction of the Palopo Samsat Information System - Andy Tri Cahyo Yarid Senobaan; Desi Revalina Putri; Nur Ilman (Poltanesa, 2025)
This study aims to analyze the user experience of using the Palopo Samsat information system, an application of information technology in public services, particularly in taxation. With the increasing use of information technology, especially in the process of administration and payment of motor vehicle taxes, this study aims to identify factors that influence user satisfaction, such as ease of access, data accuracy, speed of service, and ease of use of the system. This study uses a quantitative approach with data collection through surveys and questionnaires sent to Samsat users in Palopo City. Several new services implemented in this system, such as online tax payments, tax status updates, and tax collection services, are the main focus of this analysis. The results of the analysis show that the majority of users are satisfied with the ease of access and data accuracy, but there are several problems related to the speed of service, especially in providing system information. In analyzing the level of user satisfaction, this study uses an ease of use model that includes variables of system quality, information quality, and service quality. This study recommends that server optimization, increased service responsiveness, and better system integration be carried out to improve efficiency and user trust in the Samsat system. In addition, the development of chatbot features and increased data security are also recommended to prevent information discrepancies and improve service quality. Thus, this study is expected to provide recommendations for system improvements that can improve the quality of public services and the effectiveness of the Samsat information system in Palopo as a whole.